2020
DOI: 10.1002/jor.24799
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and load‐induced posttraumatic osteoarthritis in the absence of fracture or surgical trauma

Abstract: Osteoarthritis is increasingly viewed as a heterogeneous disease with multiple phenotypic subgroups. Obesity enhances joint degeneration in mouse models of posttraumatic osteoarthritis (PTOA). Most models of PTOA involve damage to surrounding tissues caused by surgery/fracture; it is unclear if obesity enhances cartilage degeneration in the absence of surgery/fracture. We used a nonsurgical animal model of load-induced PTOA to determine the effect of obesity on cartilage degeneration 2 weeks after loading. Car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…46,48 Figure 2B). The finding has been confirmed in subsequent studies 51 and early evidence suggests that factors produced by gut microbes may directly regulate bone tissue quality. 52 We recently found that the effect of the gut microbiome on bone tissue material properties is not limited to growing mice; alterations to the gut microbiome in aged mice (modified from 1 to 2 years of age) also lead to similar reductions in bone tissue mechanical properties.…”
Section: Can the Microbiome Help Prevent Periprosthetic Joint Infecmentioning
confidence: 63%
See 1 more Smart Citation
“…46,48 Figure 2B). The finding has been confirmed in subsequent studies 51 and early evidence suggests that factors produced by gut microbes may directly regulate bone tissue quality. 52 We recently found that the effect of the gut microbiome on bone tissue material properties is not limited to growing mice; alterations to the gut microbiome in aged mice (modified from 1 to 2 years of age) also lead to similar reductions in bone tissue mechanical properties.…”
Section: Can the Microbiome Help Prevent Periprosthetic Joint Infecmentioning
confidence: 63%
“…Guss and colleagues found that changes in the constituents of the gut microbiome in growing mice lead to impaired bone tissue strength at skeletal maturity—in the absence of noticeable changes in bone quantity 50 (Figure 2B). The finding has been confirmed in subsequent studies 51 and early evidence suggests that factors produced by gut microbes may directly regulate bone tissue quality 52 . We recently found that the effect of the gut microbiome on bone tissue material properties is not limited to growing mice; alterations to the gut microbiome in aged mice (modified from 1 to 2 years of age) also lead to similar reductions in bone tissue mechanical properties 53 .…”
Section: What Causes Poor Bone Tissue Quality?mentioning
confidence: 72%
“…The basic characteristics of participants in human studies was shown in Supplementary Table 2 . The animal studies included three non-intervention experiments ( 37 , 55 , 56 ), seven experiments about disturbing GMB to exacerbate OA ( 21 , 38 , 40 , 41 , 46 , 48 , 49 ), and 11 experiments about regulating GMB dysbiosis to alleviate OA ( 39 , 42 44 ; 45 , 47 , 50 54 ). The risk of bias was evaluated for each study ( Figures 2 , 3 ; Supplementary Table 3 , 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…They found that the Osteoarthritis Research Society International (OARSI) score of female and male mice was significantly decreased after antibiotic treatment, as well as the serum levels of IL-6, TNF-a, calcium ion, and MMP-13. Luna et al (49) performed cyclic loading to induce OA in mice and investigated the effects of HFD-induced obesity on cartilage damage and GMB. The study did not find an effect of obesity on cartilage damage, only a significant change in GMB composition was observed.…”
Section: Animal Studies: Intervention Studies About Gmb Dysbiosis Exa...mentioning
confidence: 99%
“…Most notable was the lowest diversity of gut microbiome in the antibiotic‐treated TLR5KO group, which had the lowest cartilage damage among the four groups, suggesting the role of the microbiome in mediating the cartilage damage. In another study examining the effects of antibiotic treatment of TLR5KO mice, gut microbiome richness was found to be reduced 46 . Severely obese wild‐type mice fed with HFD, TLR5KO mice, and antibiotic‐treated TLR5KO mice had distinct gut microbiome diversity from one another, with notable differences at the class level (Verrucomicrobiae, Gammaproteobacteria, Erysipelotrichi, Mollicutes, Actinobacteria, and Coriobacteria).…”
Section: Animal Studiesmentioning
confidence: 99%